Dziecko – podmiot czy „przedmiot” uroczystości, zwyczajów i obrzędowości szkolnych? Próba zarysu problemu na przykładzie instytucji oświatowo- -wychowawczych i opiekuńczych w Łodzi końca XIX i w XX wieku - Sosnowska, Joanna (Biuletyn Historii Wychowania, 2018)
The purpose of the work was to present the type, course and meaning of the widely defined school celebrations with children as the main actors in the multinational and multi-religious contexts of Lodz in the 19th and 20th centuries. The author’s intention was to provide an answer to the key question of this study: did children prepared for school celebrations and events and participating in them, were the subjects of the education process or rather, were they tool on which the school (e.g. boards of charitable organizations, municipal or church authorities, education authorities, teachers, or carers) exerted its influence. To what extent did the organization of school events result from the establishment’s rituals and to what extent was the need for this kind of “ceremonies” affected by the local (social and political) environment? The historical background of the work is the time before the Great War, the years of 1914–1918, and the time of Interwar Poland. Bearing in mind the historical and pedagogical aspects referred to above, the author tried to present events with young participants held in institutions run by charitable organizations (by 1914); ceremonies related to the promotion of students of initial years of municipal schools (1914–1918) and celebrations and ceremonies held in care institutions for girls and boys. The research is based on archive materials, press materials, historical and contemporary literature on the subject.